Transdermal delivery of risedronate using chemical enhancers for improved skin penetration - Nam, So Hee (Creative Pharma Assent, 2025)
Background: Risedronate sodium (RIS) is effective for bone diseases but has low bioavailability and severe side effects. This study investigates the use of hydrophilic enhancers to improve the efficiency of RIS's transdermal delivery. Methods: This study involved preparing topical samples of RIS with various enhancers, including ethanol (EtOH), dimethyl sulfoxide (DMSO), Dimethylene glycol monomethyl ether (DGME), and propylene glycol (PG). In vitro permeation tests were conducted using hairless mouse skin in Franz diffusion cells, and skin irritation tests were performed on mice. Results: The cumulative amount of RIS after 24 hours significantly increased with penetration enhancers: 6.02 μg/cm² (RIS alone), 90.22 μg/cm² (20% DGME), 67.31 μg/cm² (20% PG), 266.31 μg/cm² (20% DMSO), and 784.52 μg/cm² (20% EtOH). EtOH showed a dose-dependent increase, with 1,302.76 μg/cm² at 50% concentration. Further experiments using DMSO and EtOH at concentrations of 5% and 10% identified the optimal permeation enhancement as follows: 201.36 ± 31.6 μg/cm2 (5% DMSO), 183.03 ± 31.6 μg/cm2 (10% DMSO), 261.71 ± 164.93 μg/cm2 (5% EtOH), 569.21 ± 197.67 μg/cm2 (10% EtOH). Discussion: EtOH and DMSO significantly enhanced RIS penetration by modifying the skin's structure. The study suggests that adjusting the concentration of these enhancers can control the penetration profile, offering a promising alternative to oral delivery. Conclusions: This study demonstrated that chemical enhancers significantly improved the skin penetration of RIS. The transdermal delivery of RIS can help reduce the side effects of oral delivery of the drug and thus improve patients’ compliance.